Implementation of Differentiated Learning with the Utilization of Merdeka Mengajar Platform in Elementary School - Afifah, Marwa Faridatul; Nisa, Choirun (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to explore the implementation of differentiated learning in grade VI Indonesian language subjects by utilizing the Merdeka Mengajar Platform application at Gadungan Elementary School. Methodology: The method used is descriptive qualitative. Data were collected through in-terviews, observations, and document studies related to the implementation of differentiated learning and the use of the Merdeka Mengajar Platform ap-plication. Data were analyzed through data reduction, data presentation, and conclusion drawing. Assessment techniques for checking data validity are technical triangulation and source triangulation. Results: The results showed that differentiated learning has been implemented at Gadungan Elementary School, especially in Indonesian language subjects in class VI with the support of sources from the Merdeka Mengajar platform. Variations in differentiated learning methods can increase student motiva-tion and creativity. In addition, differentiated learning also has a positive impact on the development of Pancasila Student Profile characters, such as cooperation, creativity, and critical reasoning. The utilization of the Merdeka Mengajar platform is still not optimal, especially when using the assessment and reflection features. However, using the Merdeka Mengajar platform helps teachers find references to learning resources or teaching modules, ex-amples of formative assessments, and relevant learning videos. Applications/Originality/Value: Differentiated learning by utilizing the Merdeka Mengajar Platform has the potential to increase the effectiveness of the implementation of the inde-pendent curriculum.